Nomophobia and lifestyle: Smartphone use and its relationship to psychopathologies - Soraia Gonçalves; Paulo Dias; Ana-Paula Correia (Computers in Human Behavior Reports, 2020)
In the last decade, smartphone use increased exponentially among the population mainly among adolescents and young adults. Today, people are constantly clinging to the smartphone in many situations of their life, even though this activity can have physical and psychological negative consequences. Through the popularization of smartphones, a new dependency was born, nomophobia, defined as the fear of being away from one’s smartphone. This study analyzes the propensity of young adults (18–24 years old) towards nomophobia and lifestyle. A sample of 495 participants showed a positive and moderate correlation between nomophobia and psychopathological symptoms. Interpersonal sensitivity, obsession-compulsion, and the number of hours of smartphone use per day were identified as strong predictors of nomophobia. Results show that smartphone use, and feelings of personal inadequacy and inferiority are relevant when explaining nomophobia.